Dosimetria em altas doses e atenuação de raios X de nanocompósitospoliméricos de PVDF/OG - Juliana Viegas Pereira (2017)
In the present thesis polymer nanocomposites were developed by filling polyvinylidene fluoride (PVDF) homopolymers with graphene oxide nanosheets (GO). To investigate its dosimetric characteristics, pure samples of PVDF and PVDF filled with graphene oxide (PVDF/GO) were irradiated with doses ranging from 100 kGy to 1000 kGy, using a Co-60 source with activity of 52,600 Ci. For characterization purposes, several analytical techniques were employed, including spectroscopic and thermometric investigations. In pure PVDF samples the results revealed the appearing of one optical absorption band at 1591 cm-1, whose intensity is unequivocally related to the delivered dose. Due to its linear dose behavior, these bands revealed potential for dosimetry purposes. Spectroscopic techniques indicated higher degradation products in the pure PVDF samples. The introduction of 1.88% GO sheets induced an increase of the maximum decomposition temperature in pristine and postirradiated PVDF/GO nanocomposites. It has been observed that the addition of dispersed GO sheets in PVDF prevents the formation of spherulites and increases the resistance of the crystalline fraction to the radiation damages. Study on dosimetric properties indicates that UV-Vis absorption at 250 nm can be used for high dose dosimetry in the range of 100 to 1000 kGy. Results of the investigations involving PVDF/GO as X rays attenuators showed that the addition of small quantities of crystalline graphitic materials has provided a significant increase in the mass attenuation coefficient. Particularly, an extraordinarily higher attenuation has been observed for PVDF/GO when compared to the other crystalline graphitic-based nanocomposites. In a comparative evaluation, it was observed that the Aluminum mass attenuation coefficient curve presents an extremely peculiar coincidence to the PVDF/GO (1.88%) nanocomposite ones, for X rays energies ranging from 6.5 keV to 22.1 keV. It is concluded that in addition to the remarkable properties of chemical, mechanical and electromechanical properties involving graphene applications, it adds peculiar characteristics of X-ray shielding, allowing the development of nanocomposites that are easy to synthesize, resulting in more flexible, light and cheaper products.